2016
DOI: 10.1093/ckj/sfw105
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care for patients with end-stage renal disease: approach to treatment that aims to improve quality of life and relieve suffering for patients (and families) with chronic illnesses

Abstract: Providing end-of-life care to patients suffering from chronic kidney disease (CKD) and/or end-stage renal disease often presents ethical challenges to families and health care providers. However, as the conditions these patients present with are multifaceted in nature, so should be the approach when determining prognosis and treatment strategies for this patient population. Having an interdisciplinary palliative team in place to address any concerns that may arise during conversations related to end-of-life ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…If there is any uncertainty in prognosis and no consensus is reached related to dialysis, then a time-limited trial of dialysis may be provided [ 4 ]. Palliative care should be considered for patients suffering from disease complications at any EoL stage [ 45 ]. A multidisciplinary care team is necessary to provide physical, psychosocial, religious, and spiritual support for ESRD patients who opt out of or refuse dialysis.…”
Section: Advance Care Planning and Renal Palliative Carementioning
confidence: 99%
“…If there is any uncertainty in prognosis and no consensus is reached related to dialysis, then a time-limited trial of dialysis may be provided [ 4 ]. Palliative care should be considered for patients suffering from disease complications at any EoL stage [ 45 ]. A multidisciplinary care team is necessary to provide physical, psychosocial, religious, and spiritual support for ESRD patients who opt out of or refuse dialysis.…”
Section: Advance Care Planning and Renal Palliative Carementioning
confidence: 99%
“…Many patients who received dialysis also suffer from multiple comorbidities, and 1‐year mortality rates following initiation of dialysis are 22–24% in patients 75 years or older. Dialysis patients are often reported to feel less independent, to be less able to participate in social activities and have an overall decline in functional status and quality of life . In order to fill this gap of renal care, end‐of‐life care has been considered by encouraging effective communication between the patient, the family and the medical team to offer symptoms relief and optimize the quality of life.…”
Section: Explore the Causes Of Ckd: Customer To Datamentioning
confidence: 99%
“…Dialysis patients are often reported to feel less independent, to be less able to participate in social activities and have an overall decline in functional status and quality of life. 19 In order to fill this gap of renal care, end-of-life care has been considered by encouraging effective communication between the patient, the family and the medical team to offer symptoms relief and optimize the quality of life. In addition, the 'Hospice Palliative Care Regulation Amendment' and 'Patient's Self-determination Right Act, Taiwan' will also give a big support to the end-of-life care.…”
Section: Palliative Carementioning
confidence: 99%
“…This finding is mirrored in other specialties dealing with life-limiting illnesses including oncology, cardiology, and nephrology. 29,30 A large part of this low number is driven by the physician's own discomfort at having these conversations. Many physicians report being concerned that discussions centered on disease progression and end-of-life wishes may distress their patients or cause them to "give up," despite the fact that studies have shown evidence to the contrary 31,32 ; several studies centered on open communication in advanced cancer patients revealed that all patients reported wanting honesty from their providers, as well as some indication of their overall prognosis.…”
Section: Advance Care Planning In Phmentioning
confidence: 99%